2016
DOI: 10.1515/ace-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Interference in the Investment Process During the Realization of a Shopping Centre – A Case Study

Abstract: During the planning and controlling of the construction process, most attention is focused on risk analysis, especially in the context of final costs and deadlines of the investment. In this analysis, the primary and most significant concern is the proper identification and quantification of events, which on a certain level of probability may affect the development process. This paper presents the result of a risk analysis for a particular building object, made after completion of the investment and accepting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…W tym celu przydatne mogą być metody analizy wielokryterialnej. Maja one szereg zalet [4]: umożliwiają przyjęcie do oceny dużej liczby kryteriów; jednoznacznie szeregują wybór wariantu najlepszego, obiektywizują oceny ekspertów; ich algorytmy obliczeniowe nie są trudne do implementacji komputerowej. Narzędzi wielokryterialnego wspomagania procesu podejmowania decyzji jest wiele, a możliwości ich szerokiego zastosowania w budownictwie zaprezentowano m.in.…”
Section: Wprowadzenieunclassified
See 1 more Smart Citation
“…W tym celu przydatne mogą być metody analizy wielokryterialnej. Maja one szereg zalet [4]: umożliwiają przyjęcie do oceny dużej liczby kryteriów; jednoznacznie szeregują wybór wariantu najlepszego, obiektywizują oceny ekspertów; ich algorytmy obliczeniowe nie są trudne do implementacji komputerowej. Narzędzi wielokryterialnego wspomagania procesu podejmowania decyzji jest wiele, a możliwości ich szerokiego zastosowania w budownictwie zaprezentowano m.in.…”
Section: Wprowadzenieunclassified
“…Umożliwia to porównanie cech, nie tylko ilościowych, ale również jakościowych. Autorzy zastosowali jedną metodę kodowania: kodowanie wg Neumana-Morgensterna, jedną z częściej stosowanych w zagadnieniach z obszaru podejmowania decyzji w budownictwie [4,7,8]. Jej szczegółowy opis można odnaleźć w pracy [9].…”
Section: Tabelaunclassified
“…Successful completion of a construction project means that its completion has been completed within the assumed budget, at the scheduled time, in accordance with the expected quality, and taking into account all investor requirements. In the literature, many studies can be found regarding the analysis of construction projects due to their costs (Juszczyk, Leśniak & Zima, 2018;Wieczorek, Plebankiewicz & Zima, 2019), time (Ibadov & Kulejewski, 2015;Krzemiński, 2017), organizational aspects (Hoła, 2015;Kozlovska, Mackova & Spisakova, 2016;Lendo-Siwicka, Połoński & Pawluk, 2016;Nowotarski, Pasławski & Matyja, 2016;Grzyl, Miszewska-Urbańska & Apollo, 2017;Nowogońska & Cibis, 2017;Hanak & Korytarova, 2018), safety issues (Hoła & Szóstak, 2015), or the use of innovative solutions in construction fi led (Mrówczyńska, 2011;Kapliński, 2018). Yet, it is the calculation of costs that is one of the most important aspects of construction projects, both from the investor's and contractor's point of view.…”
Section: Introductionmentioning
confidence: 99%
“…There are many papers devoted to the analysis of construction projects in terms of time [16,24], costs [18,28,32,40], logistics [43], process organizational aspects [12,13,14,19,22,26,37,38], work safety [15], innovative solutions [19] and project contracting [23]. There are many factors affectingthe course of a construction project in time, and frequently they can be foreseen already at the works planning stage.…”
Section: Introductionmentioning
confidence: 99%